Interaction and self-correction - Satne, Glenda L. (Frontiers in Psychology, 2014)
In this paper I address the question of how to account for the normative dimension involved in conceptual competence in a naturalistic framework. First, I present what I call the Naturalist Challenge (NC), referring to both the phylogenetic and ontogenetic dimensions of conceptual possession and acquisition. I then criticize two models that have been dominant in thinking about conceptual competence, the interpretationist and the causalist models. Both fail to meet NC, by failing to account for the abilities involved in conceptual self-correction. I then offer an alternative account of self-correction that I develop with the help of the interactionist theory of mutual understanding arising from recent developments in Phenomenology and Developmental Psychology.